THE NEXUS OF PRODUCTION QUALITY CONTROL AND THE PERFORMANCE OF SACHET WATER FIRMS IN BORI, RIVERS-STATE - Akam, Uche G.; Edwin M., Dapper (International Journal For Research In Business, Management And Accounting, 2021)
This study was targeted at examining the nexus between production quality control and the performance of sachet water firms Bori, Rivers-state. The key performance indicators of interest to the researchers include; operational efficiency, customer satisfaction and corporate growth. The study adopted the survey approach in its design and a five point likert scale questionnaire was the major tool for data gathering. The data gathered was analyzed with Mann-Whitney test (U) and spearman’s correlation coefficient test using the 20.0 version of SPSS. The findings of the paper shows a high connectivity between production quality control on and the performance of sachet water firms in Bori as the three variables that were used to proxy performance showed different but all positive level of significant relationship. The researchers therefore recommend among others that sachet water firms in Bori should see and take production quality control as a strategic continuous process and not just one time event to secure regulatory approval.